A systematic review and meta-analysis of sleep and circadian rhythms disturbances in individuals at high-risk of developing or with early onset of bipolar disorders. (April 2022) - Scott, Jan; Etain, Bruno; Miklowitz, David; Crouse, Jacob J.; Carpenter, Joanne; Marwaha, Steven; Smith, Daniel; Merikangas, Kathleen; Hickie, Ian
Abstract: Sleep and circadian rhythms disturbances (SCRD) in young people at high risk or with early onset of bipolar disorders (BD) are poorly understood. We systematically searched for studies of self, observer or objective estimates of SCRD in asymptomatic or symptomatic offspring of parents with BD (OSBD), individuals with presentations meeting recognised BD-at-risk criteria (BAR) and youth with recent onset of full-threshold BD (FT-BD). Of 76 studies eligible for systematic review, 35 (46%) were included in random effects meta-analyses. Pooled analyses of self-ratings related to circadian rhythms demonstrated greater preference for eveningness and more dysregulation of social rhythms in BAR and FT-BD groups; analyses of actigraphy provided some support for these findings. Meta-analysis of prospective studies showed that pre-existing SCRD were associated with a 40% increased risk of onset of BD, but heterogeneity in assessments was a significant concern. Overall, we identified longer total sleep time (Hedges g: 0.34; 95% confidence intervals:.1, .57), especially in OSBD and FT-BD and meta-regression analysis indicated the effect sizes was moderated by the proportion of any sample manifesting psychopathology or receiving psychotropic medications. This evolving field of research would benefit from greater attention to circadian rhythm as well as sleep quality measures. Highlights: Sleep and circadian rhythm disturbances (SCRD) in young people at high risk of or with recent onset of bipolar disorders (BD) are poorly understood. We categorized early expression of BD into three groups: offspring of parents with BD (OSBD), Bipolar-at-Risk (BAR) individuals andcases with adolescent/early adulthood BD onset (FT-BD). A systematic search of the literature identified 76 relevant publications of which 35 provided data that could be included in random effects meta-analyses. BAR and FT-BD populations demonstrated eveningness chronotype and social and circadian dysrhythmias. Actigraphy studies demonstrated longer total sleep time especially in OSBD and FT-BD.